A comparative study of polypropylene/chloroprene rubber and recycled polypropylene/chloroprene rubber blends - Nurul Azra, Bakaruddin; Salmah, Husseinsyah, Dr. Ir.; Yusrina, Mat Daud (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.